I-PDEK: Microscope-integrated OCT–assisted pre-Descemet endothelial keratoplasty. Issue 12 (December 2021) - Sharma, Namrata; Devi, Chandra; Agarwal, Rinky; Bafna, Rahul Kumar; Agarwal, Amar
Abstract : Four patients with pseudophakic corneal edema were subjected to pre-Descemet endothelial keratoplasty (PDEK) under the direct guidance of microscope-integrated optical coherence tomography (i-OCT). i-OCT facilitated successful type 1 big bubble formation during donor preparation, debridement of the hypertrophic epithelium, planning and placement of surgical wounds, descemetorrhexis with removal of remnant Descemet membrane tags, and identification of correct donor orientation and interface details. It was also possible to discern the stability of intraocular lens, flat iris configuration, adequate stromal hydration, and wound apposition on i-OCT. Preoperative visual acuity was counting fingers (50%), 0.78 logMAR (25%), and 1.48 logMAR (25%), whereas postoperative visual acuity was 0.6 logMAR (50%) and 0.3 logMAR (50%). At 6-months of follow-up, all grafts were clear and well attached, the mean central corneal thickness, graft size, graft thickness, and endothelial cell loss were 557.25 ± 13.45 μm, 7.75 ± 0.20 mm, 25.5 ± 2.64 μm, and 21.6 ± 0.02%, respectively. To conclude, i-OCT helped during various surgical steps of PDEK.